(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This paper explores the critical role that dictionaries play in the process of learning English. It examines various types of dictionaries, their features, and how they support vocabulary acquisition, comprehension, and language use. The study also discusses the benefits of digital dictionaries and mobile applications in enhancing the learning experience. The findings indicate that dictionaries are indispensable tools for English learners, aiding in effective communication and deeper understanding of the language.